RELIGIOUS AND MYTHOLOGICAL SYMBOLS IN UZBEK AND ENGLISH TEXTS - Xalikova Dildora Normurodovna; Karriev Adkham (Innovate Conferences, 2025)
Symbolism is a powerful semiotic resource through which cultures encode collective experiences, spiritual beliefs, and mythological narratives. This study examines the representation of religious and mythological symbols in Uzbek and English texts across various genres, including folklore, classical literature, modern works, and sacred traditions. Using a qualitative comparative semiotic approach, the research analyzes symbols such as celestial bodies, natural elements, animals, moral and spiritual metaphors, and sacred numbers to identify similarities and differences between the two cultures. The findings show that while many symbols share universal mythic foundations, their meanings diverge significantly due to the influence of Islam in Uzbek culture and Christianity and Greco-Roman mythology in English culture. The study provides insights for comparative linguistics, cultural semiotics, and translation studies by demonstrating how symbols reflect cultural memory and shape literary interpretation.
Keywords: symbolism; mythological symbols; religious symbolism; Uzbek literature; English literature; cultural semiotics; archetypes; comparative literature.